The Term of Mental Illness in Javanese - Ari Wulandari; Yanuar Bagas Arwansyah; Nanda Saputra (Britain International for Academic Research (BIAR-Publisher), 2022)
This study uses a linguistic anthropological approach to qualitative research design or research context. The term “mental illness” are covered depends on Javanese language context. The data collection is by participating observation and interviews. Javanese language has at least two types of mental illness recognized in accordance by the cause, namely (1) natural mental illness (mental illness cause natural process), consisting of minor mental illness and serious mental illness; and (2) unnatural mental illness (mental illness cause of human or other creatures) ‘mental illness cause comes to disruption beings or spirits’. Traditional medicine is usually adjusted to cause of mental illness. From definition, classification, and traditional medicine can described Javanese’s view to mental illness.